An Exaggeration of Qur’an by the Baghdadi Mu‘tazilite: Studying Abu Tahir al-Turaythithi - Salimi, Abdulrahman al- (Manuscripta Orientalia, 2014)
The objective of this paper is to shed the light to the series of manuscripts of the treatise al-Mutashabih fi al-Qur’an ( Ambiguous [ayat] in the Qur’an ) by Abu Tahir al-Turaythithi, Mu'tazilte scholar of Baghdad. The problem discussed is the exaggeration of the Qur’an which was the point of sharp theological debates. We know comparatively well the Mu'tazilte works produced in Basra while the work by Abu Tahir al-Turaythithi reflects comprehensively the school of Baghdad. The journey of the treatise through the Muslim world as presented by its manuscripts started from Central Asia, they appeared in Yemen and Oman and finally in one of the European libraries.
Keywords: Coran – Commentaires

Ibadi Studies and Orientalism - Salimi, Abdulrahman al- (On Ibadism, 2014)
Keywords: Orientalisme – Ibadisme

Islamic art in Oman - Salimi, Abdulrahman al-; Gaube, Heinz; Korn, Lorenz (Mazoon printing, publishing & advertising, 2014)
Keywords: Arts – Oman

HOFFMANN-RUF, M., und A. AL SALIMI (Hrsg.) – Oman and Overseas. proceedings of the Inter- national Conference ‘The Ibadism of Oman - Its Overseas Development and its perception Over- seas’ held at Tübingen University, 16th-19th of May 2011. - Custers, Martin H. (Bibliotheca Orientalis, 2014)
Keywords: Recension

Early Ibāḍī theology: six kalām texts - Fazārī, ʿAbd Allāh ibn Yazīd (Brill, 2014)
Kitab al-qadar (Book of predetermination) Kitab fi l-radd ʻala Ibn ʻUmayr (Book on refutation of Ibn ʻumayr) Kitab al-radd ʻala al-mujassima (Book of refutation of the Corporalists) Kitab al-futya (Book of legal opinion) Kitab al-tawḥid fi maʻrifat Allah (Book of monotheism in the recognition of God) Kitab fi man rajaʻa ʻan ʻilmih wa-faraqa al-Nabi wa-huwa ʻala dinih – (Book about whoever reneges on his knowledge and departs from the Prophet while remaining in his religion
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle